Development of Gemini AI as a Virtual Assistant in Student’s WhatsApp Discussion Group - Ilham Alifian Firmansyah (Universitas Sebelas Maret (UNS), 2025)
Introduction: WhatsApp is a social media platform that is frequently used in Indonesia. The ease of use of WhatsApp makes people of any group of age groups use it. WhatsApp also has a group feature that can be used as a discussion platform. Most students in Indonesia joined a WhatsApp group either to share information or discuss their school tasks. But not all their WhatsApp group have their teacher as a group member because sometimes they feel uncomfortable discussing something when their teacher is in the same group. So, we need a virtual assistant to help the students answer their questions while discussing. One of the most used virtual assistants is Google Gemini AI. So, researchers recommend integrating Google Gemini AI and students’ WhatsApp discussion groups. Aim of the study: To develop a virtual assistant to increase the effectiveness of students’ discussion, providing information, answering questions, or guiding them to complete their task. Method: The method used in this research development is the waterfall. Results: The Researcher successfully developed the virtual assistant and worked as planned; it answers any question when the group participant mentions it in the WhatsApp group chat room. Conclusion: The virtual assistant has a big scalability to develop; it can be trained to a specific major, depending on its group. For the next study, researchers recommend imposing a limitation so the students do not abuse their power.